Վահաբական քարոզչության մի քանի դրսևորումների շուրջ - Փաշայան, Արաքս («Զանգակ - 97»)
The Wahhabism emerged in 1940's of eighteenth Century in Central Arabia (Nejd) from the teaching of Muhammad Ibп Abd al-Wahhab. Coming of Hanbalism it is considered to be one of the fundamental directions of Sunni Islam. Historically Wahhabism played a positive role in formation of Saudi State becoming the governmental ideology of the State. Especiatly in the beginning of 1970's (connected with the.increase of petrol pricesl Saudi Arabia (SA) tried to strengthen its political role and importance in the world of Islam. In I960's SA initiated formation of some Islamic international organizations, such as the Islamic Conference Organization, the Muslim World Lcague, etc. SA purposed to make the Islam a main functional power arguing its leadership in the Islamic world. Düring quarter Century SA made all efforts to establish Wahhabi oriented mosques, educational and rcligious centers, benevolent and humanitarian foundations. spreading Wahhabi literature all over the world via Wahhabi missioners.
Keywords: Կրոն; Քաղաքականություն; Պատմություն